Cognitive impairment in a primary healthcare population: a cross-sectional study on the island of Crete, Greece. Issue 9 (24th September 2020) - Bertsias, Antonios Konstantinos; Tsiligianni, Ioanna; Papadakis, Sophia; Zaganas, Ioannis; Duijker, George; Symvoulakis, Emmanouil K; Papadokostakis, Polyvios; Makri, Kornilia; Iatraki, Eliza; Tziraki, Chariklia; Basta, Maria; Panagiotakis, Simeon; et al.
Abstract : Objectives: Cognitive impairment is known to have a significant impact on the quality of life of individuals and their caregivers, yet it is often underdiagnosed. The objective of this study is to assess the extent of cognitive impairment among elders visiting primary healthcare (PHC) practice settings, to explore associated risk factors and discuss current care challenges for PHC providers. Design: A cross-sectional study was conducted between March 2013 and May 2014. Setting: Fourteen PHC units located in rural and urban areas of the Heraklion district in Crete, Greece. Participants: Consecutive visitors aged at least 60 years attending selected PHC practices. Primary and secondary outcome measures: The Mini-Mental State Examination (MMSE) was used to indicate cognitive status. Associations of low MMSE scores (≤23/24, adjusted for education level) with 12 socio-demographic factors, comorbidities and lifestyle factors were assessed. Results: A total of 3140 PHC patients met inclusion criteria (43.2% male; mean age 73.7±7.8 years). The average MMSE score was 26.0±3.8; 26.7±3.5 in male and 25.4±3.9 in female participants (p<0.0001). Low MMSE scores were detected in 20.2% of participants; 25.9% for females vs 12.8% for males; p<0.0001. Female gender (adjusted OR (AOR)=2.72; 95% CI 2.31 to 3.47), age (AOR=1.11; 95% CI 1.10 to 1.13), having received only primary or no formal education (AOR=2.87; 95% CI 2.26 to 3.65), alcohol intake (AOR=1.19; 95% CI 1.03 to 1.37), reporting one or more sleep complaints (AOR 1.63; 95% CI 1.14 to 2.32), dyslipidaemia (AOR=0.80; 95% CI 0.65 to 0.98) and history of depression (AOR=1.90; 95% CI 1.43 to 2.52) were associated with low MMSE scores. Conclusions: This study identified a relatively high prevalence of low MMSE scores among persons attending PHC practices in a southern European community setting and associations with several known risk factors.